The Field Guide to the North American Teenager - Philippe, Ben (New York, NY : Balzer + Bray, an imprint of HarperCollins Publishers, 2019)
When Norris, a Black French Canadian, starts his junior year at an Austin, Texas, high school, he views his fellow students as clichš from "a bad 90s teen movie."
Keywords: Interpersonal relations -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Moving, Household -- Juvenile fiction; Canadian Americans -- Juvenile fiction; Haitian Americans -- Juvenile fiction; Single-parent families -- Juvenile fiction; Interpersonal relations -- Fiction; High schools -- Fiction; Schools -- Fiction; Moving, Household -- Fiction; Canadian Americans -- Fiction; Haitian Americans -- Fiction; Single-parent families -- Fiction; Austin (Tex.) -- Juvenile fiction; Austin (Tex.) -- Fiction